2019
DOI: 10.1111/jfpe.13343
|View full text |Cite
|
Sign up to set email alerts
|

Effect of soy protein isolate on the techno‐functional properties and protein conformation of low‐sodium pork meat batters treated by high pressure

Abstract: In this study, the changes of color, emulsion stability, rheological property, and protein secondary structure attributes of pork meat batters (1% sodium chloride) treated by high pressure with different soy protein isolate were investigated. Three batters with 0, 2, and 4% soy protein isolate were prepared under 200 MPa for 10 min, respectively.The pH, emulsion stability, L* and b* values were significantly improved when added soy protein isolate, the a* value was significantly (p < .05) decreased. The pH and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 39 publications
1
18
0
Order By: Relevance
“…Meanwhile, the L* value was significantly increased, and a* and b* values were significantly decreased ( P < 0.05) at 200, 300 and 400 MPa, compared to those at 0.1 MPa; however, all L* , a* and b* values showed no significant differences. A possible reason is that HP processing can induce changes in the molecular interactions (hydrogen bonds, hydrophobic interactions, sulphydryl and electrostatic bonds) and conformation of the myofibrillar protein and SPI, which presents altered functional properties, including improved solubility and water‐holding capacity (Li et al ., 2020). In addition, HP processing could change the oxidative states of the pigment myoglobin, and the occurrence of redox reaction can be visualised using the L* , a* and b* values.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Meanwhile, the L* value was significantly increased, and a* and b* values were significantly decreased ( P < 0.05) at 200, 300 and 400 MPa, compared to those at 0.1 MPa; however, all L* , a* and b* values showed no significant differences. A possible reason is that HP processing can induce changes in the molecular interactions (hydrogen bonds, hydrophobic interactions, sulphydryl and electrostatic bonds) and conformation of the myofibrillar protein and SPI, which presents altered functional properties, including improved solubility and water‐holding capacity (Li et al ., 2020). In addition, HP processing could change the oxidative states of the pigment myoglobin, and the occurrence of redox reaction can be visualised using the L* , a* and b* values.…”
Section: Resultsmentioning
confidence: 99%
“…Storage modulus is a key index for rheological properties of meat proteins, which is in line with the elastic behaviour of the solid‐like components and directly affects the gel properties of meat batter (Li et al ., 2020). The effects of G′ on raw batters supplemented with SPI treated at different pressures from 20 to 80 °C are shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Soy protein isolate (SPI) is the main component of soy protein, and its protein content is generally higher than 90 %. Studies have shown that SPI has several functional properties, such as gelation, emulsification, and foaming [2] , [3] , and is widely used in the field of food processing [4] , [5] . However, SPI is easily affected by harsh processing conditions during processing and storage, resulting in quality deterioration.…”
Section: Introductionmentioning
confidence: 99%
“…Residual amino acids from carnosine synthesis, free amino acids, might induce the oxidative modification of proteins ( Zhang et al, 2013 ). Protein oxidation causes the unfolding of its secondary structure, which is transformed into β-sheets, β-turns ( Li et al, 2020 ), and aliphatic bending groups ( Herrero, 2008 ). Katemala et al (2021) reported that the β-sheet relative content positively correlated with the shear force of KRC, and the result was confirmed by Beattie et al (2004) .…”
Section: Resultsmentioning
confidence: 99%